2022
DOI: 10.29333/ejecs/1279
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Citizens' Satisfaction and Trust in Police as a Function of Good Governance and Cooperative Culture

Abstract: The role of police institutions in developing law-and-order situations and protecting citizens’ lives and valuables is of immense importance worldwide. Based on the social learning theory, the current study examines the extent to which police performance, accountability, and moral alignment with the community develop and enhance the trust among the citizens via an underlying mechanism of their satisfaction level with police institutions based on their services’ delivery. Data were collected from the citizens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The result of this study supports prior research ndings (seeRudhanto, 2022). The results suggested how crucial it is to recognize perceived accountability as a positive predictor of citizens' trust in municipal authorities and how valuable it is for local authorities to restore and win over local citizens' trust in the municipal administration.Likewise, in line with prior research, PTP positively and signi cantly in uences CTM (seeRudhanto, 2022). This implies that local government authorities get more trust and con dence from the citizenry when they practice transparency in their daily operations and activities.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The result of this study supports prior research ndings (seeRudhanto, 2022). The results suggested how crucial it is to recognize perceived accountability as a positive predictor of citizens' trust in municipal authorities and how valuable it is for local authorities to restore and win over local citizens' trust in the municipal administration.Likewise, in line with prior research, PTP positively and signi cantly in uences CTM (seeRudhanto, 2022). This implies that local government authorities get more trust and con dence from the citizenry when they practice transparency in their daily operations and activities.…”
supporting
confidence: 88%
“…Moreover, He and Ma (2021) reported that the perceived performance of government institutions mediates the relationship between public participation and citizens' trust. Similarly, accountability is positively and signi cantly associated with the perceived local government performance (Rudhanto, 2022;Demir et al, 2019). Likewise, Porumbescu (2017) found that transparency positively relates to the perceptions of public sector performance.…”
Section: The Mediating Role Of Citizens' Perception Of Municipal Gove...mentioning
confidence: 93%
See 2 more Smart Citations
“…Personal norms and values are referred to as characters and the values one brings up (Antrobust et al, 2019). Studies have demonstrated that the effects of norms on an individual's behaviour vary among individuals with different levels of moral values (Celestin & Kruschke, 2019;Rudhanto, 2022).…”
Section: Moral Valuesmentioning
confidence: 99%